PENGOBATAN TANAMAN JAHE YANG SANGAT BERMANFAAT DI ERA PANDEMI - Nia Kurniasih; Nurhidayati Harun; Nova Zahra; Delis Herliawati; Didin Awaludin; Iis Siti Nurhasanah (LPPM STIKes Muhammadiyah Ciamis, 2022)
In early 2020, Indonesia was shocked by an outbreak of disease from Wuhan China, namely Corona Virus Disease 2019 (Covid-19. This virus invades the body by attacking the immune system. Plants that have good immunity are ginger. However, many still see it as a spice kitchen. To find out the content of ginger that is useful during the Covid-19 pandemic, a journal literature search was conducted using Google Scholar and Pubmet. The search was carried out in October 2021. The results obtained from a journal review, that ginger contains an active compound gingerol which acts as an anti-inflammatory agent oxidant.